The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1743-0003-11-79
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive neuromodulation to improve gait in chronic multiple sclerosis: a randomized double blind controlled pilot trial

Abstract: BackgroundThis study sought to examine the effect of targeted physical therapy with and without cranial nerve non-invasive neuromodulation (CN-NINM), on the walking ability of people with MS who exhibited a dysfunctional gait. We hypothesized that subjects who received electrical stimulation would have greater improvement than those who had a control device after a 14-week intervention. Gait disturbance is a common problem for people with multiple sclerosis (MS). Current management may include exercise, pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 62 publications
(57 reference statements)
1
45
0
Order By: Relevance
“…16 Therefore, traditional therapies emphasized compensatory techniques that conserved the individual's energy. 17,18 However, this notion has been challenged by prior investigations that have shown that aerobic exercise can result in moderate improvements in the walking speed and endurance of individuals with MS while having no deleterious Neurology Section, APTA. Unauthorized reproduction of this article is prohibited.…”
Section: Introductionmentioning
confidence: 96%
“…16 Therefore, traditional therapies emphasized compensatory techniques that conserved the individual's energy. 17,18 However, this notion has been challenged by prior investigations that have shown that aerobic exercise can result in moderate improvements in the walking speed and endurance of individuals with MS while having no deleterious Neurology Section, APTA. Unauthorized reproduction of this article is prohibited.…”
Section: Introductionmentioning
confidence: 96%
“…79 Studies have shown that the tongue can be used as an effective interface for conveying electrical signals to the CNS, 1013 including sensory substitution in balance-impaired or blind people. 1417 Individuals with primary vestibular disorders using electrical stimulation of the tongue together with head-position information demonstrated sustained balance improvements beyond their final stimulation session. 13,14 In the present study, we use cranial nerve noninvasive neuromodulation (CN-NINM), a form of electrotactile stimulation delivered by a portable neuromodulation stimulator device (PoNS™ 14 ) that sends a series of small electrical pulses via a tongue electrode array to try to improve balance and gait problems in patients with MS. We also investigated whether this kind of stimulation could improve working memory in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…71 The gait of MS patients has been shown to significantly improve with the combination of exercise and a device that electrically stimulated the tongue to enhance the plasticity of the brain. 72 Functional electrical stimulation (FES) produces a contraction in a paralyzed or weak muscle that can improve function through electrical excitation of the innervating nerve. FES can be used clinically to manage foot drop in people suffering from diverse neurological conditions.…”
Section: Neuromodulation Of the Peripheral Nervous Systemmentioning
confidence: 99%